1993
DOI: 10.1105/tpc.5.7.809
|View full text |Cite
|
Sign up to set email alerts
|

Isodityrosine cross-linking mediates insolubilization of cell walls in Chlamydomonas.

Abstract: Enzymatic removal of the cell wall induces vegetative Chlamydomonas reinhardtii cells to transcribe wall genes and synthesize new hydroxyproline-rich glycoproteins (HRGPs) related to the extensins found in higher plant cell walls. A cDNA expression library made from such induced cells was screened with antibodies to an oligopeptide containing the (SP)x repetitive domains found in Chlamydomonas wall proteins. One of the selected cDNAs encodes an (SP)x-rich polypeptide that also displays a repeated YGG motif. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 44 publications
1
86
0
Order By: Relevance
“…VSP-3 m R N A levels are low in vegetative cells (as in Fig. 6D), increase for the next 2 h, and then decline as wall regeneration is completed, a pattern very similar to that seen for another vegetative wall protein, VSP-1 [53]. So, like WP6, VSP-3 is a vegetative-specific wall protein.…”
Section: Gene Expression Studiessupporting
confidence: 63%
See 4 more Smart Citations
“…VSP-3 m R N A levels are low in vegetative cells (as in Fig. 6D), increase for the next 2 h, and then decline as wall regeneration is completed, a pattern very similar to that seen for another vegetative wall protein, VSP-1 [53]. So, like WP6, VSP-3 is a vegetative-specific wall protein.…”
Section: Gene Expression Studiessupporting
confidence: 63%
“…In previous work, we demonstrated that a (SerPro)x motif is found in both zygote and vegetative cell wall proteins [53,56,57] suggesting that (SerPro)x repeats might be diagnostic for volvocalean cell wall proteins in the same manner that Ser(Pro)4 repeats are diagnostic of dicot extensins [57].…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations